An algorithm for controlling the transmission of video streams in a flying ad hoc network - M. Alghazali, Salah M.; Aljeazna, Wisam K. Mahdloom; Rasol, Murtadha N.; Polshchykov, Konstantin A.; V. Likhosherstov, Rodion (Institute of Advanced Engineering and Science, 2025)
This article discussing the enhancement of video surveillance in various territories through the implementation of a flying ad hoc network (FANET). The primary objective of the surveillance is for search and rescue operations. To optimize the quality of FANET video broadcasting, a decision-making algorithm for video stream management is introduced. This algorithm evaluates the likelihood of achieving high-quality video transmission. Depending on the assessed probabilities, the algorithm recommends one of the following actions: initiating a new video stream transmission, reducing the average length of wireless channels, or discontinuing the transmission of low-information video streams. Computational experiments demonstrate a significant improvement in the accuracy of decision-making regarding the management of video stream transmission to FANET when utilizing the proposed algorithm.